Visible-Light-Induced Enantioselective Dearomative [2+2]-Cycloaddition/Ring-Expansion Sequence of Indoles with Simple Alkenes - Hou, Liuzhen; Yang, Longqing; Liu, Xiaohua; Cao, Weidi; Feng, Xiaoming (Synlett, 2025)
Catalytic asymmetric dearomatization reactions represent a versatile platform for constructing complex optically active three-dimensional molecules. We present a visible-light-induced asymmetric dearomative [2+2] cycloaddition/ring-expansion reaction of indole derivatives with simple alkenes in the presence of a chiral N,N′-dioxide/terbium complex. This strategy provides access to a range of valuable cyclopenta[b]indoles, and its synthetic potential is further showcased through a gram-scale synthesis, potential bioactivity against human breast cancer, and further transformation into a yuehchukene analogue. A series of control and spectral experiments, as well as DFT calculations, provide compelling evidence to elucidate the reaction mechanism.
Keywords: dearomatization; photocatalysis; indoles; asymmetric catalysis; [2+2] photocycloaddition; cyclopentaindolones